Rationally designed ultrathin Ni(OH)2/titanate nanosheet heterostructure for photocatalytic CO2 reduction - Wanru Liao; Suwei Lu; Weihang Chen; Shuying Zhu; Yuzhou Xia; Min-Quan Yang; Shijing Liang (Green Chemical Engineering, 2022)
Dye-sensitized photocatalysis has been extensively studied for photocatalytic solar energy conversion due to the advantage in capturing long-wavelength photons with a high absorption coefficient. The rational integration of photosensitizer with semiconductor and cocatalyst to collaboratively operate in one system is highly desired. Here, we fabricate a Ni(OH)2-loaded titanate nanosheet (Ni(OH)2/H2Ti6O13) composite for high-performance dye-sensitized photocatalytic CO2 reduction. The ultrathin H2Ti6O13 nanosheets with negative surface charge provide an excellent support to anchor the dye photosensitizer, while the loaded Ni(OH)2 serves as an adsorbent of CO2 and electron sink of photoelectrons. As such, the photoelectrons derived from the [Ru(bpy)3]Cl2 sensitizer can be targeted transfer to the Ni(OH)2 active sites via the H2Ti6O13 nanosheets linker. A high CO production rate of 1801 μmol g-1 h-1 is obtained over the optimal Ni(OH)2/H2Ti6O13, while the pure H2Ti6O13 shows significantly lower CO2 reduction performance. The work is anticipated to trigger more research attention on the rational design and synthesis of earth-abundant transition metal-based cocatalysts decorated on ultrathin 2D platforms for artificially photocatalytic CO2 reduction.